Systematic Literature Review (SLR) Al-Qur'an-Hadith Subjects at Madrasas - Nurbani Nurbani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Al-Qur'an-Hadith is one of the subjects that must be taught to students at the Madrasah Tsanawiyah level, from the ibtidaiyah / diniyah Awaliyah level, tsanawiyah to the level of 'aliyah. Like other subjects, the subjects of the Qur'an-Hadith were also chosen as the object of research. Of course, in addition to being useful in answering related questions, it can also be useful as a reference material for research that raises the same issue, it is even expected to contribute to improving the problem-solving abilities of teachers and students in this subject in the madrasa environment as an Islamic Religious Education institution. This study uses the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles that have similar research and are related to this title. The articles used in this study were 11 national journal articles indexed by DOAJ, Sinta, Garuda, Moraref, Neliti, Base, Crossref, Copernicus and Google Schoolar. Based on this research, it is concluded that in general, the problems of the subjects of the Qur'an Hadith are still dominated by the problem of teacher competence and the success of students in following the teaching and learning process. Based on a review of the literature selected in this study, it was found that teacher competence plays an important role, especially in designing learning and inculcating good values for students as the main target in learning the Qur'an Hadith, namely being able to realize it in everyday life.